ЕFFICIENCY OF USING INTERNET LANGUAGE TRANSLATION TOOLS IN WORKING - Z. P. Aminova (Journal Park Publishing, 2022)
The paper considers internet technologies as a tool of optimizing the process of the teaching foreign languages.
Keywords: internet technologies; tool; foreign languages